Graphene functionalisations: Conserving vitrimer properties towards nanoparticles recovery using mild dissolution. (10th November 2021) - Poutrel, Quentin-Arthur; Baghdadi, Yasmine; Souvignet, Aline; Gresil, Matthieu
Abstract: Graphene epoxy nanocomposites are highly investigated for the potential to combine properties of the polymer matrix and nanofillers. Epoxy vitrimer presents many advantages compared to traditional epoxy thermoset such as stress relaxation and recycling capacity. Hence, this study explores the effect of graphitic nanoparticles on an epoxy vitrimer formulation and potential to recover those from the crosslinked structure by mild dissolution. Graphene nanoplatelets (GNP), graphene oxide (GO), reduced graphene oxide (rGO) and silane bearing epoxy functionalised graphene nanoplatelets (GPTS-GO) are added to the vitrimer at 0.1, 0.5 and 1 wt % loading. Evolution in tensile properties and XRD reveal that nanoparticles bond with the vitrimer matrix when having functionality (GO, rGO and GPTS-GO). Overall, an improvement of tensile mechanical properties is reported while remaining chemically crosslinked and achieving complete relaxation. The vitrimer properties are then exploited to recover nanoparticles via a simple dissolution/washing method. Chemical investigation (XPS, RAMAN, and XRD) of recovered particles shows no traces of polymer. Nonetheless, few chemical changes are observed: nanoparticles with low functionality (GNP and rGO) received additional hydroxyl functions after recycling. Reversibly, highly functionalised particles (GO and GPTS-GO) undergo cleaving of functional units during the extraction process. Graphical abstract: Image 1